PERSPECTIVES OF PERFECTION OF CRIMINAL-PROCEDURAL LEGISLATION OF RK ON THE USE OF RESULTS ORD IN EVIDENCE (Journal of actual problems of jurisprudence, 2019)
We believe that such a procedure for drafting documents guarantees the admissibility andthe relevance of evidence and its sources, formed on the basis of the presented resultsoperational search activities and allows you to solve tasks, aimed atoptimization and improvement of the investigation process.